Virus meningo-encephalitis in Austria: 3. Pathogenic and immunological properties of the virus - Verlinde, J. D. (1955)
Two virus strains were isolated from the central nervous systems of two fatal human cases during an epidemic of encephalomyelitis in Austria. Monkeys, mice, and chick embryos proved susceptible; rabbits and guinea-pigs were refractory. The experimental disease in monkeys was characterized by acute meningo-encephalomyelitis, which was localized particularly in the grey matter of the brain stem, the cerebellum, the medulla, and the anterior horns of the spinal cord. The virus produced discrete lesions on the chorioallantoic membrane of the chick embryo. In monkeys, viraemia was demonstrated for a period of at least 6-8 days before the development of the clinical illness. The virus was shown to be closely related to that of Russian spring-summer encephalitis. Neutralizing and complement-fixing antibodies could be demonstrated in patients' sera.